2012
DOI: 10.1128/cvi.05428-11
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Taenia solium Taeniasis Coproantigen Is an Early Indicator of Treatment Failure for Taeniasis

Abstract: ABSTRACTTaenia soliumcauses taeniasis and cysticercosis, a zoonotic complex associated with a significant burden of epilepsy in most countries. Reliable diagnosis and efficacious treatment of taeniasis are needed for disease control. Currently, cure can be confirmed only after a period of at least 1 month, by negative stool microscopy. This study assessed the performance of detection by a coproantigen enzyme-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 28 publications
0
39
0
4
Order By: Relevance
“…Furthermore, we collected post-treatment stool samples in the first round of mass treatment and followed persons who had results that indicated that they had a tapeworm with the most sensitive test available to verify that the parasites were killed. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we collected post-treatment stool samples in the first round of mass treatment and followed persons who had results that indicated that they had a tapeworm with the most sensitive test available to verify that the parasites were killed. 22 …”
Section: Discussionmentioning
confidence: 99%
“…It may be that the absence of a gold standard to diagnose taeniasis makes it difficult to know who is infected, leading to a challenge in assessing efficacy. An estimated efficacy of 77.9% (95%CI: 66.7%-86.2%) of niclosamide is probably the best available [30]. According to a review [31], the efficacy of praziquantel (5mg/kg) ranges between 67% and 94% while a dose of 10 mg/kg would be 100% efficacious, but the assessment of taeniasis in these studies were problematic.…”
Section: Introductionmentioning
confidence: 99%
“…cannot be differentiated, but a species determination may be possible if mature, gravid proglottids or the scolex are present. Recently developed coproantigen and molecular assays are more sensitive than stool examination, but neither is widely available 26,27. Serologic methods, which are available only in research settings, may be used to identify T. solium tapeworm carriers; however, because antibody persists for an unknown period after treatment, serologic testing may produce false-positive results if a patient has been treated for taeniasis in the recent past 28…”
Section: The Diseasementioning
confidence: 99%